Potential strain to produce bioprotein from cheaper carbon source: Hope for millions - Jamal, Parveen; Alam, Md. Zahangir; Umi, Nurul (Science Publications, 2007)
Bioprotein production is one of the most promising breakthroughs of biotechnological innovations. Due to its increasing demand, the efficient strains, substrate and method must be used for high yield product. In this study, screening of five different cerivisiea, Mucor hiemalis and Thricoderma harzianum, was done for bioprotein production by liquid state bioconversion of wheat flour as a cheaper carbon source. Bioconversion was done with fixed wheat flour concentration of 2% (w/v) at a temperature 27°C, agitation of 150 rpm with 2% inoculum (106 spores mLˉ1). Biomass production was recorded continuously for six days and the protein content was also determined every day. From the observed results, Mucor hiemalis was found to be the most potential strain with biomass of about 11.48 g Lˉ1 on the fourth day of treatment. With this promising result, the amount of bioprotein was further increased to 21.89 g Lˉ1 by optimizing few process factors. Further optimization developments are in progress. This study may provide a better alternative in agricultural products by converting cheaper carbon source to valuable and quality product bioprotein, which can be used as supplement and additive in the animal feed and food as well as in chemical and pharmaceutical industries.